Path Following of Autonomous Vehicle in 2D Space Using Multivariable Sliding Mode Control. (20th August 2014) - Ji, Daxiong; Liu, Jian; Zhao, Hongyu; Wang, Yiqun
Abstract : A solution to the path following problem for underactuated autonomous vehicles in the presence of possibly large modeling parametric uncertainty is proposed. For a general class of vehicles moving in 2D space, we demonstrated a path following control law based on multiple variable sliding mode that yields global boundedness and convergence of the position tracking error to a small neighborhood and robustness to parametric modeling uncertainty. An error integration element is added into the "tanh" function of the traditional sliding mode control. We illustrated our results in the context of the vehicle control applications that an underwater vehicle moves along with the desired paths in 2D space. Simulations show that the control objectives were accomplished.